1998
DOI: 10.1364/ao.37.007624
|View full text |Cite
|
Sign up to set email alerts
|

Phase-shifter calibration and error detection in phase-shifting applications: a new method

Abstract: The phase-shifting technique is used in optical metrology to evaluate the local phase of a fringe pattern. Accurate calibration of the shifting device is often essential but sometimes hardly possible because of deviations of the fringe pattern from the ideal sinusoidal shape and because of a nonconstant phase shift between consecutive frames. We introduce a new technique for calculating the phase shift between frames even in the presence of high noise and nonsinusoidal fringe patterns. In addition, this techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 2 publications
0
23
0
Order By: Relevance
“…That is why a new comparison methodology has been proposed. Its main principle is based on a paper by Gutman and Weber [17] where a novel method of inspect− ing a phase−shifter calibration quality by extending the idea of a mean phase−shift angle histogram (routinely used in such cases) to a special 2D histogram -the lattice site -was proposed. The lattice site approach was recently applied to determine other phase shifting experimental errors, e.g., nonlinear recording and tilt−shift errors [5,6].…”
Section: Quantitative Methodsmentioning
confidence: 99%
“…That is why a new comparison methodology has been proposed. Its main principle is based on a paper by Gutman and Weber [17] where a novel method of inspect− ing a phase−shifter calibration quality by extending the idea of a mean phase−shift angle histogram (routinely used in such cases) to a special 2D histogram -the lattice site -was proposed. The lattice site approach was recently applied to determine other phase shifting experimental errors, e.g., nonlinear recording and tilt−shift errors [5,6].…”
Section: Quantitative Methodsmentioning
confidence: 99%
“…In order to obtain any of the position-dependent terms (I 0 (x, y), c (x, y) or U(x, y)), it is necessary to have at least three linearly independent equations for I(x, y). Different equations are obtained by assigning different values to the arbitrary phase a for different interferograms (Van Wingerden, Frankena, and Smorenburg 1991;Gutmann and Weber 1998). While only three interferograms are needed for recovery of the optical phase, it has been shown that using a larger number of interferograms will reduce the impact of experimental errors during acquisition (Hariharan, Oreb, and Eiju 1987).…”
Section: Phase Shifting Interferometrymentioning
confidence: 99%
“…Classical interferometry has the drawback that an ambiguity on the slope of the surface is obtained. This ambiguity is overcome through phase shifting interferometry, which implies the introduction of an additional optical phase (Kinnstaetter et al 1988;Gutmann and Weber 1998;Iwai et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than two interferograms are needed for this technique. During the recording process, many environmental factors along with the precision of the phase shifter always cause phase-shift errors, which induce errors on the retrieved object wavefronts [8][9][10][11]. Some methods with random phase shifts and many phase-shift retrieval algorithms are useful in decreasing the negative effects of these errors [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%